Occupational Health Implications of Hazardous Waste Management: A U.S. Perspective on Global Risks, Compliance Benchmarks, and Local Innovation - Long Holt, Kimberly (Indonesian Journal of Advanced Research, 2025)
Hazardous waste management standards in the United States, the United States Resource Conservation and Recovery Act, and OSHA HAZWOPER standards, are the international standard of hazardous waste management. This paper will discuss the occupational health outcomes in the four common waste streams and how the Hierarchy of Controls the exposure in the U.S. setting. The synthesis of global evidence that the study created shows that there are critical transboundary risks of e-waste exports and that there are occupational exposures in low-resource countries. Some of the field-tested low-cost adoptions are introduced in the paper: rudimentary exhaust systems, mobile manifesting, and reusable protective equipment protocols. The innovations can help the U.S professionals involved in the management of resource-bounded operations to stay in line with compliance and tackle the local and global dangers of the supply chain. Findings indicate that joint regulatory implementation and innovation-based remedies help in mitigating waste-related job sickness expenses that amount to 10-15 billion dollars per year.